Optimization Of The Use Of Laboratory And Simulators In Practical Learning Of Marine Engineering Study Program In Malahayati Merchant Marine Polytechnic - Bagus Wicaksono, R. (International Journal of Education and Digital Learning (IJEDL), 2022)
According to the KBBI, a laboratory is a certain place or room and so on which is equipped with equipment for conducting experiments. The laboratory has various equipment that is able to support conducting experiments. The laboratory serves to improve the skills and expertise of researchers in using the equipment available in the laboratory. In addition, the laboratory also functions as a learning tool for students to be able to understand and understand all abstract knowledge so that it is concrete and real. While the simulator is a tool to perform simulations. Malahayati Merchant Marine Polytechnic is one of the vocational colleges that has laboratory infrastructure and simulators for nautical studies, marine engineering and ship electrical systems. This study aims to see the extent to which the optimization of the use of practical learning media in laboratories and simulators in supporting vocational education at the Malahayati Merchant Marine Polytechnic.